Near-infrared photoimmunotherapy for the treatment of skin disorders. (3rd April 2022) - Russo, Irene; Fagotto, Laura; Colombo, Anna; Sartor, Emma; Luisetto, Roberto; Alaibac, Mauro
ABSTRACT: Introduction: Near-Infrared Photoimmunotherapy (NIR-PIT) is a novel molecularly targeted phototherapy. This technique is based on a conjugate of a near-infrared photo-inducible molecule (antibody-photon absorber conjugate, APC) and a monoclonal antibody that targets a tumor-specific antigen. To date, this novel approach has been successfully applied to several types of cancer. Areas covered: The authors discuss the possible use of NIR-PIT for the management of skin diseases, with special attention given to squamous cell carcinomas, advanced melanomas, and primary cutaneous lymphomas. Expert opinion: NIR-PIT may be an attractive strategy for the treatment of skin disorders. The main advantage of NIR-PIT therapy is its low toxicity to healthy tissues. Cutaneous lymphocyte antigen is a potential molecular target for NIR-PIT for both cutaneous T-cell lymphomas and inflammatory skin disorders.